دور وسائل الإعلام والاتصال الحديثة في حماية المجتمع من مخاطر برامج الإلحاد المعاصر - المرغني د. عادل عاشور محمد (المجلة الدولية لعلوم الإعلام والاتصال, 2024)
الملخص: يهدف البحث إلى التعرف على آثار العولمة والصورة النمطية والذهنية التي يقدمها الإعلام الحديث للتأثير على المجتمع الإسلامي وسلوكياته ومدى الترويج الخفي لإلحاد المعاصر. وقد استخدام المنهج الاستقرائي، للوصول لملخص يمكن الاستفادة منه. ونتيجة لذلك تركز البحث على كيفية إنشاء منظومة إعلامية دينية تقوم بإقناع الناس وتدعيم الصورة الذهنية للقيم الأخلاقية للدين الإسلامي، وقد حدد الباحث عدة مقترحات يمكن أن تسهم في مواجهة برامج الإلحاد المعاصر، ولعل أبرزها: الدعم المادي لوسائل الإعلام والاتصال الحديثة لمحابة الإلحاد المعاصر. صناعة محتوى إعلامي يحارب الأعمال المسيئة لصورة الإسلام، ولتجنب الخضوع للإعلام الغربي. بناء خطاب ديني متوازن يحارب الإلحاد المعاصر. تطبيق مبدا الرقابة على وسائل الإعلام والاتصال عبر إنشاء هيئة رصد المحتوى تحجب الإعمال المسيئة للهوية والقيم الدينية. الكلمات المفتاحية: الإعلام، الإلحاد المعاصر، حماية المجتمع. Abstract: The research aims to identify the effects of globalization and the stereotypical and mental image presented by modern media to influence Islamic society and its behaviors and the extent of the hidden promotion of contemporary atheism. The inductive approach was used to reach a summary that can be used. As a result, the research focused on how to create a religious media system that persuades people and strengthens the mental image of the moral values of the Islamic religion. The researcher identified several proposals that could contribute to confronting contemporary atheism programs, perhaps the most prominent of which are: - Financial support for modern media and communication to favor contemporary atheism. - Creating media content that combats acts that harm the image of Islam, and to avoid submission to Western media. - Building a balanced religious discourse that combats contemporary atheism. - Implementing the principle of censorship on media and communication by establishing a content monitoring body that blocks actions that are offensive to identity and religious values. Keywords: media, contemporary atheism, protecting society.